The Calendar Systems of Sulawesi Ethnic Groups from the Perspective of Falak Science - Syarif, Muh Rasywan; Chotban, Sippah; Syam, Hikmatul Adhiyah; Surya, Nurfadillah; Safiai, Mohd Hafiz (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
The calendar systems of the ethnic groups in Sulawesi highlight a gap in understanding regarding the extent to which these traditional systems align with, differ from, or complement contemporary astronomical and Islamic time-keeping practices. Despite these communities’ rich, culturally embedded knowledge of time-division based on celestial movements, there has been minimal research on how these indigenous systems engage with scientific astronomy or are shaped by religious influences. Furthermore, there is a lack of comparative studies examining how each community’s calendar system reflects their unique cultural identities, cosmologies, and adaptations to environmental changes. This study examines the calendar systems of popular Sulawesi ethnic groups which are the Bugis, Mandar, and Toraja through the lens of falak science. This study employs a qualitative approach, utilizing document analysis, interviews, and observations as its primary methods. The findings indicate that these Sulawesi ethnic groups hold a rich repository of traditional knowledge on calendar systems, which aligns closely with foundational astronomical principles. Addressing these gaps could deepen insights into the preservation of cultural heritage and the potential integration of traditional knowledge with contemporary scientific and religious calendar practices.